2021
DOI: 10.1002/anie.202107036
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐Responsive Gene Editing to Reduce Tumor Thermal Tolerance for Mild‐Photothermal Therapy

Abstract: Near‐infrared (NIR)‐light‐triggered photothermal therapy (PTT) is usually associated with undesirable damage to healthy organs nearby due to the high temperatures (>50 °C) available for tumor ablation. Low‐temperature PTT would therefore have tremendous value for clinical application. Here, we construct a hypoxia‐responsive gold nanorods (AuNRs)‐based nanocomposite of CRISPR‐Cas9 for mild‐photothermal therapy via tumor‐targeted gene editing. AuNRs are modified with azobenzene‐4,4′‐dicarboxylic acid (p‐AZO) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 46 publications
0
62
0
Order By: Relevance
“…For these hypoxic stimuli-responsive nanoplatforms, the AZO groups are generally used to link hydrophilic and hydrophobic moieties in amphiphilic molecules, which can self-assemble into nanoparticles under physiological conditions and disassemble to release the loaded contents under hypoxic conditions by breaking the AZO groups [ 293 297 ]. Therefore, breakage of the AZO linker can cause the cleavage of hydrophilic groups when the designed nanoparticles reach the hypoxic tumor microenvironment, leading to enhanced cellular internalization and tumor accumulation of nanoparticles [ 294 , 298 , 299 ]. For example, Zhang et al [ 300 ] synthesized a hypoxic-degradable nanocarrier functionalized with AZO-containing hydrophobic groups to encapsulate the chemotherapeutic agent camptothecin and photosensitive therapeutic agent chlorin e6 for laser-augmented synergistic chemo-photodynamic therapy.…”
Section: Stimuli-responsive Targeting Strategiesmentioning
confidence: 99%
“…For these hypoxic stimuli-responsive nanoplatforms, the AZO groups are generally used to link hydrophilic and hydrophobic moieties in amphiphilic molecules, which can self-assemble into nanoparticles under physiological conditions and disassemble to release the loaded contents under hypoxic conditions by breaking the AZO groups [ 293 297 ]. Therefore, breakage of the AZO linker can cause the cleavage of hydrophilic groups when the designed nanoparticles reach the hypoxic tumor microenvironment, leading to enhanced cellular internalization and tumor accumulation of nanoparticles [ 294 , 298 , 299 ]. For example, Zhang et al [ 300 ] synthesized a hypoxic-degradable nanocarrier functionalized with AZO-containing hydrophobic groups to encapsulate the chemotherapeutic agent camptothecin and photosensitive therapeutic agent chlorin e6 for laser-augmented synergistic chemo-photodynamic therapy.…”
Section: Stimuli-responsive Targeting Strategiesmentioning
confidence: 99%
“…Although PTT can increase the local temperature of the body to over 50°C and kill tumor cells, it can also cause damage to normal tissues and carry the risk of recurrence or metastasis ( Gao et al, 2019 ). Li et al applied a low oxygen responsive gold nanorods that can carry sgRNA targeting HSP90α ( Li et al, 2021 ). Due to the hypoxic state of the tumor microenvironment, the azo group of the nano-complex is selectively reduced by overexpression reductase, resulting in the release of Cas9 and subsequent HSP90α gene knockout, which reduces the thermal resistance of cancer cells.…”
Section: Applications and Effects Of Gene Editing Based On Nano-drug ...mentioning
confidence: 99%
“…Up to now, some research revolving around this topic has been reported. For example, multi-functional nanoplatforms based on Au nanorods, 13 zirconium-ferriporphyrin metal–organic frameworks (MOFs), 23 MnO 2 , 33 WS 2 , 34 black phosphorus, 35 graphene, 36 and carbon nanotubes, 36 have been developed for co-delivery of PTAs and therapeutic gene molecules. Despite encouraging results obtained through these approaches, there are still several stumbling blocks for the clinical translation of PTT–GT strategies: (i) sophisticated synthesis and stepwise modification procedures make the nanoplatforms lack homogeneity and are difficult to produce at a large scale.…”
Section: Introductionmentioning
confidence: 99%